2016
DOI: 10.1002/cmdc.201500534
|View full text |Cite
|
Sign up to set email alerts
|

Different Binding Modes of Small and Large Binders of GAT1

Abstract: Well-known inhibitors of the γ-aminobutyric acid (GABA) transporter GAT1 share a common scaffold of a small cyclic amino acid linked by an alkyl chain to a moiety with two aromatic rings. Tiagabine, the only FDA-approved GAT1 inhibitor, is a typical example. Some small amino acids such as (R)-nipecotic acid are medium-to-strong binders of GAT1, but similar compounds, such as proline, are very weak binders. When substituted with 4,4-diphenylbut-3-en-1-yl (DPB) or 4,4-bis(3-methylthiophen-2-yl)but-3-en-1-yl (BTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…Despite these failures, the substitution of positions different from the amino function (e.g., in compounds 6 and 7 ) appears to be an interesting means for the development of potential new GABA uptake inhibitors. Based on molecular modeling the unsubstituted ( R )‐nipecotic acid [( R )‐ 6 ] preferably adopts a binding pose in which the piperidine nitrogen atom faces the intracellular side, whereas for the larger inhibitor tiagabine ( 2 ) the binding pose of the piperidine ring is switched with the nitrogen and the attached arylalkyl residue facing the extracellular side of the transporter . On the basis of these results, we concluded that substitutions particularly at positions 4 or 5 with an appropriate spacer and lipophilic residue could yield GABA uptake inhibitors in which the binding pose of the piperidine ring is retained relative to that of unsubstituted ( R )‐ 6 .…”
Section: Introductionmentioning
confidence: 96%
“…Despite these failures, the substitution of positions different from the amino function (e.g., in compounds 6 and 7 ) appears to be an interesting means for the development of potential new GABA uptake inhibitors. Based on molecular modeling the unsubstituted ( R )‐nipecotic acid [( R )‐ 6 ] preferably adopts a binding pose in which the piperidine nitrogen atom faces the intracellular side, whereas for the larger inhibitor tiagabine ( 2 ) the binding pose of the piperidine ring is switched with the nitrogen and the attached arylalkyl residue facing the extracellular side of the transporter . On the basis of these results, we concluded that substitutions particularly at positions 4 or 5 with an appropriate spacer and lipophilic residue could yield GABA uptake inhibitors in which the binding pose of the piperidine ring is retained relative to that of unsubstituted ( R )‐ 6 .…”
Section: Introductionmentioning
confidence: 96%
“…A prominent selective inhibitor of mGAT1 is the nipecotic acid derivative tiagabine ( 5 ), which is in clinical use (pIC 50 =6.88±0.12; Figure ) . Further examples with enhanced affinity toward mGAT1 are NO711 and DDPM‐2571, which are derived from 3 with an oxime functionality in the alkyl side chain (NO711: pIC 50 =6.83±0.06; DDPM‐2571: pIC 50 =8.27±0.03; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas various studies describe inhibitors of mGAT1 with nipecotic acid and guvacine substructures, only a few are known concerning mGAT1 inhibitors derived from pyrrolidine‐3‐acetic acid ( 4 ). Nevertheless, the preparations of miscellaneous pyrrolidine‐3‐acetic acid derivatives containing different lipophilic residues linked by alkyl, alkenyl, or alkynyl chains to the pyrrolidine nitrogen have been reported since the late 1980s; most examples are provided by a patent, but the pharmacological characterizations at GABA transporters are rather limited . One example is the racemic N ‐(4,4‐diphenylbut‐3‐en‐1‐yl) derivative of pyrrolidine‐3‐acetic acid, ( R , S )‐ 8 , and its enantiomer, ( S )‐ 8 , which were found to be potent and selective GABA uptake inhibitors of a GABA transporter corresponding to mGAT1 in the case of ( R , S )‐ 8 and mGAT1 for ( S )‐ 8 (( R , S )‐ 8 : IC 50 =0.12 (0.10–0.15) μ m determined on rat brain tissue, which is known to preferentially contain the rGAT subtype 1; ( S )‐ 8 : pIC 50 =5.99±0.11; Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrobenzo[c][1,2,5]oxadiazol-4-yl)piperidine-3-carboxylic acid (rac-5): According to GP with racnipecotic acid (rac-1) (26.0 mg, 0.201 mmol) in aqueous solution of Na 2 CO 3 (9.6 ml) and NBD-F (40.5 mg, 0.221 mmol) in CH 3 CN (3 ml). TLC: R f = 0.12 (CH3 CN/ CH 3 OH = 95:5). TLC: R f = 0.12 (CH3 CN/ CH 3 OH = 95:5).…”
mentioning
confidence: 99%